Value added convenience food from composite sorghum-maize-sweet potato flour blends - TEGEYE, MESHACK; KAUR, AMARJEET; KAUR, JASPREET; SINGH, HIRA (The Indian Journal of Agricultural Sciences, 2019)
This study conducted at Punjab Agricultural University in the year 2017, was aimed at development of value added nutritious convenience food, i.e. cookies from flour blends of sorghum, maize and sweet potato. Individual flours of these underutilized crops were studied for their chemical, physical and functional properties. Blends were prepared from the flours and divided into two lots. In the first lot maize flour (MF) was fixed at 10% of the blend, sorghum flour (SF) was varied from 80-40% while sweet potato flour (SPF) was varied from 10-50%. In the second lot, SF was fixed at 10%, while maize flour was varied from 80-40% and SPF from 10-50%. Cookies prepared from each blend were evaluated for organoleptic characteristics. The most acceptable cookies were studied for their physicochemical characteristics. Results revealed that SPF had the maximum carbohydrate and potassium contents on dry weight basis. Sweet potato flour also had the highest water solubility index (WAI), water absorption index and fat absorption index (FAI). Based upon sensory evaluation, cookies prepared from two blends, viz. SF:MF:SPF=50:10:40 and from SF:MF:SPF=10:60:30 were most acceptable to the sensory evaluation panel. The selected cookies were rich in carbohydrates, Î²-carotene, vitamin C, minerals calcium and potassium and were gluten-free. These could serve as nutritious convenience food for the celiac patients. This study would also help in value addition of underutilized food sources such as sorghum, maize and sweet potato.